Indikator yang Mempengaruhi Peningkatan Mutu Pendidikan di Prodi Pendidikan Sejarah Universitas Islam Sumatera Utara - Anita Silviana; Suya Aymanda Nababan; Muhammad Ricky Hardiyansya; Muhammad Adika Nugraha; Latifah Hanum (Keguruan, 2023)
Regulation number 20 of 2003 concerning the state school system states that community development aims to grow capacity and shape individuals as well as the progress of the state in order to make state life more broad-minded. However, in educational organizations, various obstacles have been traced that interfere with the most common way of achieving quality training as found in the History Education Study Program of the Islamic University of North Sumatra, where efforts to work on the existing nature of training have not been ideal. Various things hinder the improvement of the nature of non-ideal teaching, including: (1) an administrative framework that is not functioning properly, (2) the incompatibility of existing educational programs with the demands of current needs, (3) the nature of showing insufficient staff, (4) there is no student discipline, (5) and there are problems and solidarity between teachers and staff. In circumstances like this, a position of authority is needed that functions to improve and improve the existing framework so that change can occur from now on.